Perception of Road Users and Stakeholders Towards Traffic Management Plan at Work Zone Area - Saedin, Hisam Masry; Mohd Lazi, Mohd Khairul Afzan; Umar, Aliyu Mani; Hassan, Sitti Asmah; Hashim, Hanini Ilyana Che; Hasan, Mohd Zulfabli; Yacoob, Teh Zaharah (Recent Trends in Civil Engineering and Built Environment, 2025)
The rapid development of Malaysia today contributes towards an increase in road users. High traffic on the highway and construction of road upgrading and maintenance work have a high risk of accidents. Therefore, a perfect and efficient traffic management plan must be enhanced to avoid road accidents. An efficient traffic management plan can ensure that traffic runs smoothly at an acceptable level while reducing the risk of road accidents. This study aims to evaluate the comprehension and implementation of the parties directly involved in the traffic management plan during road construction, upgrading work, or repairs as well as road users. This will be achieved through a well-structured questionnaire. This study case is carried out along the Projek Menaiktaraf Laluan 7 Persimpangan Lencongan Barat Ke Persimpangan Simpang Tiga Kemboja, Kedah Darul Aman is about 14.3 km long. The study indicates that those responsible for road construction (upgrading and maintenance work) have a good understanding of the Traffic Management Plan and follow the guidelines provided in the Arahan Teknik Jalan (ATJ) 2C/85 Pindaan 2017 (Manual on Traffic Control Devices). Moreover, the study reveals that road users are satisfied with the Traffic Management Plan carried out during the construction work.